Una larga travesía hasta el agua ebook Basada en una historia real (a long walk to water spanish edition). - Park, Linda Sue (2020)
This high-quality Spanish-language book can be enjoyed by fluent Spanish speakers as well as those learning the language, whether at home or in a classroom. Una larga travesía hasta el agua, bestseller del New York Times, comienza como dos historias, que se van alternando, sobre dos niños de once años en Sudán, una niña en 2008 y un niño en 1985. La niña, Nya, va a buscar agua a un estanque que está a dos horas de caminata desde su hogar; cada día, hace dos viajes hasta el estanque. El niño, Salva, se convierte en uno de los "niños perdidos" de Sudán, refugiados que recorren a pie el continente africano en búsqueda de sus familias y de un lugar seguro en el que vivir. Soportando todas las adversidades –la soledad, el ataque de rebeldes armados, el contacto con leones y cocodrilos asesinos–, Salva es un superviviente, y su historia se cruza con la historia de Nya de una manera sorprendente y movilizadora. The New York Times bestseller A Long Walk to Water begins as two stories, told in alternating sections, about two eleven-year-olds in Sudan, a girl in 2008 and a boy in 1985. The girl, Nya, is fetching water from a pond that is two hours' walk from her home: she makes two trips to the pond every day. The boy, Salva, becomes one of the "lost boys" of Sudan, refugees who cover the African continent on foot as they search for their families and for a safe place to stay. Enduring every hardship from loneliness to attack by armed rebels to contact with killer lions and crocodiles, Salva is a survivor, and his story goes on to intersect with Nya's in an astonishing and moving way.